Improving Critical Thinking Skills Using Problem Based Learning on the Media Flash Card - Erma, Erma; Koeswanti, Henny Dewi; Giarti, Sri (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study is to improve students' critical thinking skills using the Problem Based Learning model aided by flash card media. The research method used is a class action research method. The subjects of the study were the 5th grade students of SD St. Theresia Massudirini 77 with 40 students. The results of observations in the pre-cycle that the critical thinking skills of students in the category are quite critical (15%). Based on these problems, the researchers made improvements to the classroom action research, using the Problem Based Learning model aided by Flash Card media. The results showed that the critical thinking skills of students in the quite critical category were (32.5%) in the first cycle and during the second cycle increased to (75%).